MODEL ATMOSPHERES OF PECULAR CARBON GIANTS - Pavlenko, Ya. V.; Yakovina, L. A. (Одеські астрономічні публікації, 2008)
We calculated 240 model atmospheres of carbon giants of high carbon abundances (2800 ≤ Teff ≤ 3400 K, 0.06 ≤ log(C/O) ≤ 2.7). The set of models was calculated in process of analysis by spectral synthesis of spectral energy distribution of the evolved carbon star DY Per shown photometric features of R CrB type stars. The majority of these models are metal deficient (-3.5 ≤ [Fe/H] < 0), part of them are calculated with hydrogen deficiency (1/9 ≤ H/He < 9/1). Model atmosphere calculations were carried out in the framework of classical approaches with account of the relevant opacity sources in carbon stars. The opacity sampling method was used to calculate the opacity due to atomic and molecular line absorption.